2019
DOI: 10.1016/j.parkreldis.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Combined cerebral atrophy score in Huntington's disease based on atlas-based MRI volumetry: Sample size calculations for clinical trials

Abstract: Introduction: A volumetric MRI analysis of longitudinal regional cerebral atrophy in Huntington's disease (HD) was performed as a read-out of disease progression to calculate sample sizes for future clinical trials. Methods: This study was based on MRI data of 59 patients with HD and 40 controls recruited within the framework of the PADDINGTON study and investigated at baseline and follow-up after 6 and 15 months. Automatic atlas-based volumetry (ABV) of structural T1-weighted scans was used to calculate longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
14
1
1
Order By: Relevance
“…This is consistent with previous findings suggesting early degeneration of these structures with varying degrees of atrophy and/or neuronal loss depending on the disease stage (Aylward, ; Aylward et al, ; van den Bogaard et al, ; Faria et al, ; Paulsen et al, ; Rosas et al, ; Tabrizi et al, ). The longitudinal analyses detected the progression of significant volumetric reduction in the caudate, putamen and thalamus, which is in line with the reported atrophy gradient in early symptomatic HD patients in longitudinal studies (Aylward et al, ; Domínguez et al, , ; Hobbs, Barnes, et al, ; Hobbs, Henley, et al, ; Johnson et al, ; Müller et al, ; Tabrizi et al, ; Vandenberghe et al, ). Likewise, this subcortical volumetric atrophy is consistent with the vast toxicity resulting from the mutant huntingtin gene to medium spiny neurons of caudate‐putamen nucleus (Plotkin & Surmeier, ; Ross & Tabrizi, ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This is consistent with previous findings suggesting early degeneration of these structures with varying degrees of atrophy and/or neuronal loss depending on the disease stage (Aylward, ; Aylward et al, ; van den Bogaard et al, ; Faria et al, ; Paulsen et al, ; Rosas et al, ; Tabrizi et al, ). The longitudinal analyses detected the progression of significant volumetric reduction in the caudate, putamen and thalamus, which is in line with the reported atrophy gradient in early symptomatic HD patients in longitudinal studies (Aylward et al, ; Domínguez et al, , ; Hobbs, Barnes, et al, ; Hobbs, Henley, et al, ; Johnson et al, ; Müller et al, ; Tabrizi et al, ; Vandenberghe et al, ). Likewise, this subcortical volumetric atrophy is consistent with the vast toxicity resulting from the mutant huntingtin gene to medium spiny neurons of caudate‐putamen nucleus (Plotkin & Surmeier, ; Ross & Tabrizi, ).…”
Section: Discussionsupporting
confidence: 79%
“…These findings suggest that though there are few locations of cortical atrophy that survive the cross‐sectional statistical analysis, the global cortical neurodegeneration begins in the early stages of the disease and remains as the disease progresses, as has been suggested in cross‐sectional studies modeling progressive cortical thinning in HD (Nopoulos et al, ; Rosas et al, ; Tabrizi et al, ). Although a recent longitudinal report has identified atrophy in all cortical lobes with most progressive volume loss in parietal lobes (Müller et al, ), in our study the longitudinal volumetric changes were observed in the frontal cortices belonging to the motor system, followed by the parietal lobes. This variability in the spatial and temporal dynamics of cortical degeneration (Johnson et al, ) between both clinical populations might be driven by the smaller sample size used in our study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…A recent study using standardized analyses to compare imaging data from large scale prospective studies (PREDICT-HD, IMAGE-HD, and TRACK-HD) determined that volumes of the caudate, putamen, and globus pallidus had consistent large effect sizes across studies and provided greater statistical power than clinical markers [94], suggesting that, to date, structural MRI is the strongest candidate marker for use in clinical trials. The early detection of striatal atrophy via MRI in premanifest HDGCs, including young adults, means that neuroprotective treatments could start, and their effects may be tracked, as early as 15-20 years before symptoms manifest [18,52,[95][96][97][98][99]. Despite much evidence showing the usefulness of MRI-detected striatal atrophy in monitoring HD state and progression, the current study and only a few other preclinical studies have demonstrated the feasibility of using in vivo MRI to detect or monitor the effects of neuroprotective agents in HD mouse models [91,[100][101][102].…”
Section: Discussionmentioning
confidence: 99%
“…Charakteristisches Zeichen der Huntington-Krankheit im zerebralen MRT ist eine Atrophie des Nucleus caudatus, die in koronaren Schnitten besonders deutlich ist. Das Ausmaß dieser Atrophie kann als Verlaufsparameter herangezogen werden [7]. Im Verlauf der Erkrankung zeigt sich darüber hinaus eine globale Hirnvolumenminderung.…”
Section: Zusatzdiagnostikunclassified